DOI: 10.1007/978-0-387-84839-6_26
|View full text |Cite
|
Sign up to set email alerts
|

On QoS Mapping in TDMA Based Wireless Sensor Networks

Abstract: Recently, there have been many efforts to develop Wireless Sensor Networks (WSN), but no one can deny the fact that QoS support is still one of the least explored areas in this domain. In this paper, we present QoS support in WSN while highlighting the QoS mapping issue, a complex process in which QoS parameters are translated from level to level and we present a case study of a TDMA tree-based clustered WSN, where accuracy and density on the user level are mapped to bandwidth on the network level. We end our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In this paper, our study extends our previous work presented in [14], in order to cover any kind of trees, that is, our tree could have any number of nodes in its respective clusters, regardless of their depth. Leaf nodes (on level 4) sense data, and forward it to their parent nodes in each cluster, which in turn forward it to their parent nodes, until the data arrives to the sink (level 1).…”
Section: Problem Statement and Assumptionsmentioning
confidence: 93%
See 1 more Smart Citation
“…In this paper, our study extends our previous work presented in [14], in order to cover any kind of trees, that is, our tree could have any number of nodes in its respective clusters, regardless of their depth. Leaf nodes (on level 4) sense data, and forward it to their parent nodes in each cluster, which in turn forward it to their parent nodes, until the data arrives to the sink (level 1).…”
Section: Problem Statement and Assumptionsmentioning
confidence: 93%
“…In [12], the authors have identified the following QoS parameters tradeoffs between accuracy, delay, energy and density. In [14], the authors computed the TDMA superframe length as a function of the network density, mapping the network density (a user level QoS parameter) to bandwidth in a balanced-tree based WSN.…”
Section: Related Workmentioning
confidence: 99%
“…The total activity of a mote extends to multiple levels -or layers -each having its own procedure and parameters to calculate QoS. The overall performance is derived from the combination and cross layer code collaboration [1], and as stated in [2] does not necessarily means optimal performance in every layer.…”
Section: Introductionmentioning
confidence: 99%
“…The total activity of a mote extends to multiple levels -or layers -each having its own procedure and parameters to calculate QoS. The overall performance is derived from the combination and cross layer code collaboration (Masri W.,Mammeri Z.,2008), and as stated in (Bernd-Ludwig Wenning et al, 2008) does not necessarily means optimal performance in every layer.…”
mentioning
confidence: 99%